Current Trend on Preparation, Characterization and Biomedical Applications of Natural Polysaccharide-based Nanomaterial Reinforcement Hydrogels: A Review - A.Z. Najihah; Mohamad Zaki Hassan; Zarini Ismail (Elsevier, 2024)
Indexed by WOS/Scopus/ERA